Manajemen Pengelolaan Masjid Al-Kahfi di Pesantren Terpadu Al-Kahfi Bogor Dalam Upaya Membentuk Karakter Santri yang beriman dan bertakwa - Moh. Ibrahim; Maemunah Sa’diyah (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2022)
As a center of Islamic civilization, mosque must be well organized. Because the function of the mosque is not only for ritual activities but also it can be used as a place to give good education about Islam to produce future generation with a good faith and believe in Allah ﷻ. Like our prophet Muhammad ﷺ he used mosque as a place to give education and to develop their morality, to share and to improve knowledge, give physical training, war technique, organize a wedding, arrange strategies for moslem economy, central for Islam information, place for discuss and to socialize, and also place to collect the money from all Keywords: Management, Organize, Mosque, Character.